Preparation, characterization, and antibacterial activity of plaunotol and plaunoi extracts complexed with hydroxypropyl-β-cyclodextrin - Wai Mi Aung; Sarunyoo Songkro; Supreedee Songkharak; Nattha Kaewnopparat; Juraithip Wungsintaweekul (Elsevier, 2022)
Croton stellatopilosus (Plaunoi) leaves accumulate several diterpenes and possess various pharmacological activities. The present study aimed to prepare, characterize and assess the antibacterial activity of inclusion complexes prepared by mixing plaunotol (PL) or plaunoi extract (PE) with cyclodextrins (CD), including α-CD, β-CD, γ-CD, and hydroxypropyl-β-cyclodextrin (HP-β-CD). The inclusion complexes were characterized using SEM, XRD, DSC, and FT-IR and evaluated for aqueous solubility and thermal stability. The PL and PE lyophilized complexes with HP-β-CD were further evaluated for their antibacterial activity against acne-causing bacteria. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of PL, PE, and the inclusion complexes evaluated using the agar dilution method revealed that the MIC and MBC values of the inclusion complexes were lower than those of PL or PE alone. Interestingly, the complexes had a synergistic activity with clindamycin after testing with checkerboard assay. The hydrogel containing the inclusion complex and clindamycin were assessed for antibacterial activity using the agar well diffusion method. The results indicated that the hydrogels showed significant inhibition of bacterial growth. In conclusion, the prepared solid dispersion of PL or PE with HP-β-CD could enhance antibacterial activity by increasing the drug solubility. The hydrogels containing PL or PE complex and clindamycin could be considered as a candidate for the treatment of acne vulgaris.